Blue Light Therapy: A Skin Treatment Mask using Blue Light to cure Skin Disorders - Aleena Kamal; Minahil Kamal; Bushra Mehboob; Tayaba Naz; Shoaib Zafar; Syed Muddusir Hussain (Sukkur IBA Journal of Emerging Technologies)
Skin acne and disease are the most common medical conditions that lead from mild to moderate if not treated in time. There are several treatments such as Chemical peel, Dermabrasion, and many others these hyped techniques have proven to be extremely beneficial for improving and smoothening the skin texture, through treatments with chemicals and devices. Unfortunately, such techniques have various side effects such as redness, scabbing, irritation, and swelling, which do not provide a better medical treatment. These treatments require continuous medical examination and an expert opinion. Light therapy can be used non-invasively to overcome such side effects and treat a large number of skin damages. Blue light exhibits tons of advantages to human skin by reducing sebaceous glands' activeness so that they produce low amounts of oil that ultimately hook into the pores of the skin and result in skin breakouts and acne popping. Blue light can cure severe skin conditions such as sun damage, fine lines, wrinkles, acne scars, blemishes, and much more. Blue light therapies are generally used to treat the conditions, that are present superficial and under the skin surface. In this research, the face mask has been designed and incorporated with the Blue light strips to provide the blue light on the facial skin. The microcontroller has been programmed to control the intensity and time during the therapy session. This skin treatment mask has proven to be a pain-free and effective procedure to make the skin look healthy and beautiful. Statistical analysis of the results revealed promising outcomes: 60-70% success rates were observed in participants with mild to moderate skin conditions, while even in severe cases, significant improvements were noted with success rates ranging from 25-50%. The results have been incredible and satisfactory in improving the skin conditions of the user.